An exploration of emergency nurses' perceptions, attitudes and experience of teamwork in the emergency department. Issue 2 (May 2017) - Grover, Elise; Porter, Joanne E.; Morphet, Julia
Abstract: Background: Teamwork may assist with increased levels of efficiency and safety of patient care in the emergency department (ED), with emergency nurses playing an indispensable role in this process. Method: A descriptive, exploratory approach was used, drawing on principles from phenomenology and symbolic interactionism. Convenience, purposive sampling was used in a major metropolitan ED. Semi structured interviews were conducted, audio recorded, and transcribed verbatim. Transcripts were analysed using thematic analysis. Results: Three major themes emerged from the data. The first theme 'when teamwork works' supported the notion that emergency nurses perceived teamwork as a positive and effective construct in four key areas; resuscitation, simulation training, patient outcomes and staff satisfaction. The second theme 'team support' revealed that back up behaviour and leadership were critical elements of team effectiveness within the study setting. The third theme 'no time for teamwork' centred around periods when teamwork practices failed due to various contributing factors including inadequate resources and skill mix. Discussion: Outcomes of effective teamwork were valued by emergency nurses. Teamwork is about performance, and requires a certain skill set not necessarily naturally possessed among emergency nurses. Building a resilient team inclusive of strong leadership and communication skills is essential to being able to withstand the challenging demands of the ED.